(untitled) (Semiárida, 2020)
The winter burning is a tool to improve the utilization of spring regrowth of winter species in the mixed grasslands of the pampean calden forest, and to eliminate the dead material of deferred summer grasses forage. The aim of this work was to estimate the effect of burning upon the nutritive value of different morphological fractions of two species of this grassland: Piptochaetium napostaense (Pna) and Digitaria californica (Dca). The treatments were: 1. Burning; 2. No burning no early spring cut; 3. No burning and early spring cut. The following variables were measured on the forage samples, obtained at mid and end of spring: proportion of dead and live material and, within the last one, the stem and blade proportions. The percentage of crude protein and digestibility in vitro of dry matter by the modified Tilley and Terry procedure was estimated on each sample. The measurements were performed on 8 pairs of plants of Dca and Pna (experimental units). Each experimental unit was situated within randomly distributed plots. The data were analyzed by ANOVA, and the differences of means, by DMS at 5% level. The results show that, after winter burning, the regrowth of Pna in early spring has significantly lower amount of dead material, and higher nutritive value, although the burning effect disappears at the end of spring. The same trend was found in Dca, but the higher nutritive value could only be detected by digestibility.